2015
DOI: 10.1002/chem.201406019
|View full text |Cite
|
Sign up to set email alerts
|

How a Redox‐Innocent Metal Promotes the Formal Reductive Elimination of Biphenyl Using Redox‐Active Ligands

Abstract: One of the most compelling strategies for utilizing redox-active ligands is to perform redox events at the ligands to avoid accessing prohibitively high energy oxidation states at the metal center. This has been demonstrated experimentally in many systems, yet there is little understanding of the fundamental electronic structures involved with these transformations or how to control them. Here, the reductive elimination of biphenyl from [M(isq)2Ph2] (M = Ti, Zr, and Hf and isq = 2,4-di-tert-butyl-6-tert-butyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…For other transition metals (Zr, , Co, Fe ), reductive elimination can be promoted by the presence of redox-active ligands. , We , and others have demonstrated that azopyridine , ligands exhibit redox-active behavior when coordinated to transition metals. The low-lying NN π* orbital of azopyridine allows ligand reduction by one electron to generate a radical anion or two electrons to form a hydrazido dianion.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…For other transition metals (Zr, , Co, Fe ), reductive elimination can be promoted by the presence of redox-active ligands. , We , and others have demonstrated that azopyridine , ligands exhibit redox-active behavior when coordinated to transition metals. The low-lying NN π* orbital of azopyridine allows ligand reduction by one electron to generate a radical anion or two electrons to form a hydrazido dianion.…”
Section: Introductionmentioning
confidence: 95%
“…For other transition metals (Zr, 20,21 Co, 22 Fe 23−25 ), reductive elimination can be promoted by the presence of redox-active ligands. 26,27 We 28,29 and others 30−33 have demonstrated that azopyridine 34,35 ligands exhibit redox-active behavior when coordinated to transition metals.…”
Section: ■ Introductionmentioning
confidence: 99%
“…, Ti IV /Ti II ) because of its weak electronegativity, and thus efforts have been devoted to develop redox catalysis with early TMs using redox-active ligands. 3 Nevertheless, Odom et al 1 a prospected that “ this relative lack of diversity is largely due to the need for further development rather than an inherent lack of utility ”. Indeed, Tonks et al 4 recently accomplished pyrrole synthesis from alkynes and diazenes ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In that case, the geometry of the intermediate allows Ph−CF 3 reductive elimination to occur, a step which is not possible in our present system because of the relative trans positions of the phenyl and CF 3 moieties. Also, iminosemiquinone ligands have been implicated in Ph−Ph reductive elimination from a zirconium (Zr IV ) complex …”
Section: Methodsmentioning
confidence: 99%